(untitled) (Perioperaciina Medicina, 2019)
Despite the considerable efforts of the medical community, bleeding remains one of the leading causes of maternal mortality, which can be prevented. The article presents actual terminology of obstetric bleeding, problematic issues of infusion therapy and changes in the clinical guidelines of the leading world medical organizations regarding the rescission tactics of this category of patients.